Medium term health and quality of life outcomes in a cohort of children with MIS-C in Cape Town, South Africa - Frank Phoya; Claire Butters; Timothy F. Spracklen; Timothy F. Spracklen; Hanna L. Kassa; Hamza van der Ross; Chris Scott; Kate Webb; Kate Webb (Frontiers in Pediatrics)
BackgroundMultisystem inflammatory syndrome in children (MIS-C) is a disease that occurs after exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Its short-term effects have been documented but little data exist on the longer term effects of MIS-C on the health and quality of life (QOL) of patients. The objective of this study was to assess the long-term effects of MIS-C on the QOL of children.MethodsThis study was a descriptive prospective study. We included 24 participants with previous MIS-C and 20 children with juvenile idiopathic arthritis (JIA) as a positive comparator group. All children were examined and completed a paediatric quality of life (PedsQL) generic inventory score. This score was used to evaluate the School Functioning, Social, Emotional, and Physical QOL domains.ResultsAll participants with previous MIS-C made a full recovery, with no medical complaints, and normal physical examinations after a median of 705 days post acute diagnosis. The PedsQL inventory revealed that 16.7% of the children with previous MIS-C showed a deficit in the physical domain compared to 60% of the children with JIA (p < 0.001). 12.5% of the children with previous MIS-C had a deficit in their psychosocial domain which included emotional, social, and educational scores, compared to 40% of the children with JIA (p = 0.035).ConclusionsIn a cohort of 24 South African children with previous MIS-C, no medical complications were reported. A small proportion felt a prolonged effect on their QOL even after making a full recovery, although this was not as severe as children with JIA, a known chronic disease that affects QOL. This highlights the need to continue to follow up these patients and offer more comprehensive long-term care.